Efficacy of non‐invasive brain stimulation interventions in reducing smoking frequency in patients with nicotine dependence: a systematic review and network meta‐analysis of randomized controlled trials - Tseng, Ping‐Tao; Jeng, Jia‐Shyun; Zeng, Bing‐Syuan; Stubbs, Brendon; Carvalho, Andre F.; Brunoni, Andre R.; Su, Kuan‐Pin; Tu, Yu‐Kang; Wu, Yi‐Cheng; Chen, Tien‐Yu; Lin, Pao‐Yen; Liang, Chih‐Sung; et al. (Addiction (Abingdon, England), 2022)
Background and aims Nicotine is a highly addictive substance in tobacco products that dysregulates several neurotransmitters in the brain and impairs executive function. Non‐invasive brain stimulation (NIBS) methods such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are promising treatments for nicotine dependence. We investigated the efficacy and acceptability of NIBS in managing smoking cessation through a systematic review and network meta‐analysis (NMA). Methods We conducted a systematic review to identify randomized controlled trials (RCTs) that investigated the efficacy of NIBS for smoking cessation. All pairwise meta‐analyses and NMA procedures were conducted using random‐effects and frequentist models. The co‐primary outcomes were (1) the change in number of cigarettes smoked per day (change in frequency of smoking) in patients with nicotine dependence after NIBS and (2) acceptability (the dropout rate). The effect sizes for co‐primary outcomes of change in frequency of smoking and acceptability were assessed according to standardized mean difference (SMD) and odds ratio, respectively. Results Twelve RCTs with 710 participants (mean age: 44.2 years, 31.2% female) were included. Compared with the sham control, 10‐Hz rTMS over the left dorsolateral prefrontal cortex (DLPFC) was associated with the largest changes in smoking frequency [SMD = −1.22, 95% confidence interval (95% CI) = −1.77 to −0.66]. The 2‐mA bifrontal tDCS (SMD = −0.97, 95% CI = −1.32 to −0.62) and 10‐Hz deep rTMS over the bilateral DLPFC with cue provocation (SMD = −0.77, 95% CI = −1.20 to −0.34) were associated with a significantly larger decrease in smoking frequency versus the sham. None of the investigated NIBSs was associated with dropout rates significantly different from those of the sham control groups. Conclusion Prefrontal non‐invasive brain stimulation interventions appear to reduce the number of cigarettes smoked with good acceptability.